Flufenamic acid prevents behavioral manifestations of salicylate-induced tinnitus in the rat - Bal, Ramazan; Ustundag, Yasemin; Bulut, Funda; Demir, Caner Feyzi; Bal, Ali (Termedia Publishing House Ltd, 2016)
Introduction: Tinnitus is defined as a phantom auditory sensation, the perception of sound in the absence of external acoustic stimulation. Given that flufenamic acid (FFA) blocks TRPM2 cation channels, resulting in reduced neuronal excitability, we aimed to investigate whether FFA suppresses the behavioral manifestation of sodium salicylate (SSA)-induced tinnitus in rats. Material and methods: Tinnitus was evaluated using a conditioned lick suppression model of behavioral testing. Thirty-one Wistar rats, randomly divided into four treatment groups, were trained and tested in the behavioral experiment: (1) control group: DMSO + saline (n = 6), (2) SSA group: DMSO + SSA (n = 6), (3) FFA group: FFA (66 mg/kg bw) + saline (n = 9), (4) FFA + SSA group: FFA (66 mg/kg bw) + SSA (400 mg/kg bw) (n = 10). Localization of TRPM2 to the plasma membrane of cochlear nucleus neurons was demonstrated by confocal microscopy. Results: Pavlovian training resulted in strong suppression of licking, having a mean value of 0.05 +/- 0.03 on extinction day 1, which is below the suppression training criterion level of 0.20 in control tinnitus animals. The suppression rate for rats having both FFA (66 mg/kg bw) and SSA (400 mg/kg bw) injections was significantly lower than that for the rats having SSA injections (p < 0.01). Conclusions: We suggest that SSA -induced tinnitus could possibly be prevented by administration of a TRPM2 ion channel antagonist, FFA at 66 mg/kg bw.
Keywords: tinnitus; salicylate; flufenamic acid; TRPM2; experimental; rat